Knowledge of Structural System of Contemporary Architectural Approaches - Utkutuğ, Ziya; Hurol, Yonca (Chamber of Architects Bursa Section, 1992)
This article is about the knowledge of structural system and architecture within the field of architecture.
This article is about the knowledge of structural system and architecture within the field of architecture.
Keywords: knowledge, architectural approach, structural system